Modeling ex vivo tumor-infiltrating lymphocyte expansion from established solid malignancies. (1st January 2021) - Knochelmann, Hannah M; Rivera-Reyes, Amalia M; Wyatt, Megan M; Smith, Aubrey S; Chamness, Reilley; Dwyer, Connor J; Bobian, Michael; Rangel Rivera, Guillermo O; Horton, Joshua D; Lilly, Michael; Romeo, Martin J; Timmers, Cynthia D; et al.
ABSTRACT: Adoptive transfer of tumor-infiltrating lymphocytes (TIL) elicits the regression of metastatic malignancies, yet a low proportion of patients achieve complete durable responses. The high incidence of relapse in these patients highlights the need to better understand mechanisms of tumor escape from T cell control. While melanoma has provided the foundation for developing TIL therapy, much less is known about TIL efficacy and relapse in other malignancies. We sought to investigate TIL characteristics in mouse tumors which have not been studied in this setting. Here, we expanded murine TIL ex vivo in IL-2 from fragments of multiple tumor models, including oral cavity cancer models of varying immunogenicity. Additionally, TIL was expanded from pmel-1 mice bearing B16F10 melanoma, yielding an enriched population of tumor-infiltrating TCR transgenic T cells. Murine TIL are similar to human TIL in that they express high levels of inhibitory receptors (PD-1, Tim-3, etc.) and can be expanded ex vivo in IL-2 extensively. Of clinical relevance, we draw parallels between murine and human oral cavity cancer TIL, evaluating relationships between inhibitory receptor expression and function. This platform can be used by labs even in the absence of clinical specimens or clean cell facilities and will be important to more broadly understand TIL phenotypes across many different malignancies.